Reliability of simulated combat tasks performed by Brazilian Air Force cadets - Botta, Willian C.; dos Santos, José M. M. P.; Stein, Jesse A.; Padovani, Carlos R. [UNESP]; Borin, João P. (Taylor & Francis, 2024)
The Brazilian Air Force (BAF) has developed physical evaluations focused on the demands required in combat scenarios, giving rise to the Simulated Tasks (STs). Therefore, the purpose of the present study was to determine test-retest reliability and investigate learning effects of the five STs established among the BAF. Fifty-six subjects performed five STs three times, after completing a previous familiarisation session. Repeated measures analysis of variance (ANOVA) was used to determine the occurrence of learning effects, and the intraclass correlation coefficient (ICC) was used to identify the reliability of each ST. ANOVA revealed no significant differences in the subject’s scores across trials for all the STs, and the ICCs ranged from 0.75 to 0.92 (p < 0.01). In conclusion, this study identified that the five STs showed no learning effects across three successive trials and exhibited high levels of reliability.
Keywords: Combat readiness; military personnel; physical assessment; Simulated Tasks